The fungal pathogen Ustilago maydis targets the maize corepressor RELK2 to modulate host transcription for tumorigenesis - Huang, Luyao (The New phytologist, 2024)
© 2023 The Authors New Phytologist © 2023 New Phytologist Foundation.